التناص في المراسلات الدبلوماسية الدعوية وقفة تاريخية في الرسائل المحمدية - Sulaiman Ismail; Zulkipli Md Isa; Wan Moharani Mohammad; Mohammed Ibrahim; Yuslina Mohamed; Muhammad Marwan Ismail (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.